Electric Dreams: Computers in American Culture - Friedman, Ted (NYU Press, 2005)
Electric Dreams turns to the past to trace the cultural history of computers. Ted Friedman charts the struggles to define the meanings of these powerful machines over more than a century, from the failure of Charles Babbage's "difference engine" in the nineteenth century to contemporary struggles over file swapping, open source software, and the future of online journalism. To reveal the hopes and fears inspired by computers, Electric Dreams examines a wide range of texts, including films, advertisements, novels, magazines, computer games, blogs, and even operating systems. Electric Dreams argues that the debates over computers are critically important because they are how Americans talk about the future. In a society that in so many ways has given up on imagining anything better than multinational capitalism, cyberculture offers room to dream of different kinds of tomorrow.